Из истории праславянского корня *div- - Kamałova, Ałła (Acta Polono-Ruthenica, 2008)
The analysis of various dictionaries allows to reveal the stages of development of the words traced back to the common Slavic root *div-, with regard to their derivational and lexical relationships. The article focuses on the ethnological and cultural factors influencing the evolution of that family of words.